Legal Realism of Oliver Wendell Holmes Perspective: A Study of Madhiyah Livehood After Supreme Court Circular Letter Number 2 Of 2019 (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
In the context of Islamic family law studies, problems between husband, wife, and children are part of variables that cannot be separated from each other. This research issue highlights the issue of legal protection for wives and children related to their right to madhiyah livelihood, which is the husband's responsibility to fulfill it. Previously, since 2003, the Supreme Court through Decision Number 608K/AG/2003 emphasizes that the issue of madhiyah livelihood cannot be sued in court, meaning that the court is reluctant to deal with this issue. Absolutely, this decision has sparked polemics because it deprives the wife and children of their rights to the husband's responsibility in providing for the livelihood. Since 2019, the model for fulfilling the rights of wives and children to madhiyah livelihood has changed through Circular Letter Number 2 of 2019. The Supreme Court emphasized that the issue of madhiyah livelihood can be challenged in court. Of course, this decision reflects an effort to improve a more progressive legal mechanism. This study aims to analyse the basic legal considerations of the Supreme Court justices in forming this circular letter, using the legal realism theory approach from Oliver Wendell Holmes's perspective, while the method used is normative-juridical. This research resulted in the finding that Supreme Court Circular Letter Number 2 of 2019, is a form of actualization of the theory of legal realism in answering all madhiyah livelihood issues that have occurred in society. As a matter of fact that the implementation of this circular letter is not effective because it is induced by the absence of further instruments that are able to ensure whether or not the madhiyah support for wives and children is fulfilled. So this instrument is immediately needed, in order to protect and fulfil the rights of wives and children to madhiyah livelihood.